1260. Comparing the impact of six-month antiretroviral therapy dispensing to three- to five-month dispensing on viral load suppression in Kenya and Nigeria. (15th December 2022) - Cavanaugh, Joseph S; Dear, Nicole; Shah, Neha; Iroezindu, Michael; Bahemana, Emmanuel; Kibuuka, Hannah; Owuoth, John; Maswaii, Jonah; Sing'oei, Valentine; Hern, Jaclyn; Esber, Allahna; Crowell, Trevor A; et al.
Abstract: Background: Multi-month dispensing (MMD) of antiretroviral therapy (ART) decreases logistical burdens on HIV clinics and patients, which is especially important during the COVID-19 pandemic. HIV programs are scaling-up 6-month dispensing (6MD), but the impact on viral suppression (VS) has not been well-documented in programmatic settings. Methods: The African Cohort Study (AFRICOS) is an international observational study of people living with HIV (PLWH) receiving HIV care. In Nigeria and Kenya, this includes 6MD. Participants undergo semiannual viral load quantification and were included in analysis if they had complete data, documentation of MMD (self-reported) and at least two follow-up visits after initiating MMD. In stratified analyses for each country, we used multivariable logistic regression with generalized estimating equations to estimate adjusted odds ratios (aOR) and 95% confidence intervals (95%CI) comparing VS < 50 copies/mL among those who received 6MD to those given 3-5 months dispensing (3-5MD) of ART. Analyses were adjusted for age, education, employment, distance to clinic, duration on ART, ART regimen (TLD vs other) and self-reported ART adherence (≥ 1 missed dose in past 30 days). Results: Between January 30, 2020, when MMD data was first collected, and September 1, 2021, 1176 PLWH in Kenya and 272 in Nigeria had at least one visit; 285 participants from Kenya, totaling 442 visits, and 177 participants from Nigeria, totaling 382 visits, met criteria and were included in analysis. At most recent visit, VS < 50 copies/mL was documented in 266 (93.3%) participants from Kenya and 125 (70.6%) participants from Nigeria. Among the 35 participants given 6MD in Kenya, compared to 250 participants given 3-5MD, the aOR for VS was 0.42 (95%CI: 0.13-1.37); among the 91 participants given 6MD in Nigeria, compared to the 86 participants given 3-5MD, the aOR was 3.01 (95%CI: 1.70-5.31). Conclusion: The positive association between 6MD and VLS in Nigeria, as compared to 3-5MD, should prompt more aggressive scale-up of 6MD. The lack of an association in Kenya merits further investigation, but likely relates to high overall VS and few participants on 6MD. Updated data from specific geographic and demographic sub-populations is needed to inform programming as 6MD is scaled. Disclosures: All Authors : No reported disclosures.